Paracetamol to induce ductus arteriosus closure: is it valid?. Issue 6 (20th April 2013) - Allegaert, Karel; Anderson, Brian; Simons, Sinno; van Overmeire, Bart
Abstract : There remains a need for alternative medical treatments for patent ductus arteriosus (PDA) closure in extreme preterm neonates because of therapeutic failure and adverse effects associated with non-selective cyclo-oxygenase inhibitors. Reports of an association between paracetamol exposure and PDA closure in a limited number of extreme preterm neonates have been published. However, causality cannot be taken for granted because a link between the current knowledge of the clinical pharmacology of paracetamol and (patho)physiology of ductal closure is not known. In contrast to non-selective cyclo-oxygenase inhibitors, paracetamol has limited effects at peripheral sites, is a poor antithrombotic and anti-inflammatory drug and exerts its effects primarily within the central nervous system. Although paracetamol appears an effective and safe analgesic in term and near term neonates, its effectiveness and safety for PDA closure are uncertain because the drug is administered in high doses and there remain a limited number of observations in this specific subpopulation so far. Prospective comparative trials are reasonable and are urgently needed to establish both the effectiveness and safety data of paracetamol when used for this indication.